DAMPAK KEKERASAN DALAM RUMAH TANGGA TERHADAP KESEJAHTERAAN SOSIAL ANAK DI PADALAA KECAMATAN MENUI KABUPATEN MOROWALI SULAWESI TENGAH - Amin, Moh.; Roslan, Suharty; Tuwu, Darmin (Universitas Halu Oleo, 2022)
This study aims to analyze the Impact of Domestic Violence on Children's Social Welfare (Case Study in Padalaa Village, Menui District, Morowali Regency, Central Sulawesi). This type of research uses a qualitative approach with a case study method to 4 children who experience violence in Padalaa Village. Data collection techniques using observation, interviews, and documentation. The data analysis technique used a qualitative approach with the following steps, data reduction, data presentation, and conclusion drawing. There are three forms of violence committed by parents in the household against children in Padalaa Village, Menui District, Morowali Regency, Central Sulawesi, namely: physical violence, psychological violence and neglect. There are three impacts of domestic violence on children, namely: fear, stress and dropping out of school.